Stereospecific catalytic precision polymerization of 2-vinylpyridine via rare earth metal-mediated group transfer polymerization with 2-methoxyethylamino-bis(phenolate)-yttrium complexes1. Issue 38 (14th October 2015) - Altenbuchner, P. T.; Adams, F.; Kronast, A.; Herdtweck, E.; Pöthig, A.; Rieger, B.
<x xml:space="preserve">Abstract</x> C 1-Symmetric 2-methoxyethylamino-bis(phenolate)-yttrium complexes for the stereospecific polymerization of 2-vinylpyridine.